Validation of a Stability-Indicating Analytical Method Development for Simultaneous Estimation of Sodium Phenylbutyrate and Taurursodiol in Bulk and Formulation Using UPLC Method: Analytical Method Development for Simultaneous Estimation of SPB and TRS in Bulk and Formulation by UPLC - Raju, Chandrasekar; B, Sivagami; M, Niranjan Babu; Minchala, Navya (Iranian Journal of Pharmaceutical Sciences, 2025)
Sodium phenylbutyrate (SPB) and taurursodiol (TRS) are commonly used in combination therapy to treat amyotrophic lateral sclerosis, popularly known as Lou Gehrig’s disease. Using Ultra-Performance Liquid Chromatography, a stability-indicating analytical approach was designed and validated to evaluate SPB and TRS in bulk and dosage form simultaneously. Acquity UPLC BEH Shield RP-18 column (50 x 1.0 mm, 1.7µm) was used for the chromatographic separation. Next, a mobile phase was added at a 0.5 ml/min flow rate. The mobile phase included acetonitrile and 0.1% perchloric acid (20:80) v/v. Analytes were found at a wavelength of 287 nm with a photodiode array detector. An autosampler injected a five μl sample into the column, which was kept at 25 o C. SPB and TRS eluted values were 0.522 min and 1.311 min, respectively. For SPB and TRS, linearity was determined within the range of 75–450 μg/ml and 25–150 μg/ml, respectively. The method’s robustness was evaluated by purposefully changing parameters like flow rate, detector wavelength, and column temperature. Additionally, research on forced degradation in the presence of different stress conditions, such as heat, peroxide, acid, and ultraviolet light, showed that the approach could identify stable materials. In conclusion, it was found that the developed analytical method for simultaneously determining SPB and TRS in bulk and their formulation was more precise, reliable, and specific.